Possession Disorder: A Treatment Method of Islamic Psychotherapy in (El-PsikA) Al-Amien Institute of Applied Psychology - Moh Maqbul Mawardi (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2022)
This study proposed to discover the causes of patients experiencing trance disorders treated by EL-PsikA and how El-PsikA used Islamic psychotherapy methods in treating patients with trance disorders. The research method applied is a qualitative approach with data sources obtained through interviews and observations. The participants in this study consisted of two groups, namely five main participants and three triangulation participants using the snowball sampling technique. The results of this study designate the cause of the patient experiencing a trance disorder treated by El-PsikA consists of two factors, first because of a demonic disorder, and secondly because of having a trance disorder that begins with stress. While the method used in treating patients with possession disorder consists of five stages: first, the therapist performs a diagnosis to classify the symptoms of possession disorder experienced by the patient. Second, the therapist reads a prayer together with the patient-led by the therapist and is given water as an intermediary to drink to the patient. Third, if there is a reaction from the demon that has possessed the patient's body, the therapist asks the demon that possessed the patient's body to come out of the patient's body. Fourth, the therapist cleanses the devil's influence on the patient's body. Fifth, the therapist teaches patients self-therapy as a form of prevention so they don't experience a trance disorder again. Self-therapy taught is dhikr.